The Effectiveness of the Brain Out Chemistry Game as a Learning Media to Improve Students’ Learning Outcomes and Retention on the Periodic System of Elements Material: Efektifitas Permainan Brain Out Chemistry Sebagai Media Pembelajaran untuk Meningkatkan Hasil Belajar dan Retensi Peserta Didik pada Materi Sistem Periodik Unsur - Puspita, Widia Indah; Lutfi, Achmad (PendIPA Journal of Science Education, 2025)
This study aims to determine the effectiveness of using the Brain Out Chemistry learning media in This study aims to determine the effectiveness of the Brain Out Chemistry game-based media in improving students’ cognitive abilities, learning activities, and retention of learning outcomes on the Periodic System of Elements. The research was conducted at SMA Negeri 15 Surabaya involving 34 tenth-grade students using a One-Group Pretest–Posttest Design. The research instruments included cognitive tests (pretest, posttest 1, and posttest 2 as the retention test) and student activity observation sheets. Data were analyzed using the Wilcoxon Signed Ranks Test through SPSS. The results showed a significant increase between the pretest and posttest scores (sig. 0.000 < 0.05). The average score of posttest 1 was 85.87, which decreased to 76.86 in posttest 2, resulting in a retention value of 89,5%, categorized as high. Student learning activities also improved, as indicated by observation scores falling within the active category. Classically, the learning mastery rate exceeded 85%. Thus, the Brain Out Chemistry game-based media is effective because it enhances cognitive abilities, maintains learning retention, and promotes student learning activities in chemistry instruction.